The impact of primary varicella zoster virus infection on delay in diagnosis and treatment of neoplastic diseases in children – case reports - Pogorzelska, Karolina; Sawicka-Żukowska, Małgorzata; Kania, Agnieszka; Krawczuk-Rybak, Maryna (Pediatria Polska - Polish Journal of Paediatrics, 2019)
Primary varicella zoster virus (VZV) infection is highly contagious and life-threatening in immunocompromised patients. Children treated for neoplastic disease are at increased risk of severe illness and fatal outcomes. Varicella zoster infection (VZI) may cause diagnostic difficulties and result in the delay in anticancer therapy. We present the cases of four children diagnosed with neoplastic diseases and chickenpox infection simultaneously. Two patients were diagnosed with acute lymphoblastic leukaemia (ALL), one with acute myeloblastic leukaemia (AML), and one with Wilms tumour. Initially all patients received targeted and symptomatic treatment against VZV infection, and then they were reassigned to chemotherapeutic treatment. Three children received intravenous acyclovir for seven days, and one received oral treatment. The patient diagnosed with Wilms tumour, after receiving actinomycin-D, developed veno-occlusive disease with a very acute course. Mean delay in chemotherapy due to VZI was eight days. None of the patients died as a result of the infection or oncological disease.